Formation Constants of Complexes of Disalicylamide with Co(II), Ni(II), Cu(II) and Zn(II) Formation Constants of Complexes of Disalicylamide with Co(II), Ni(II), Cu(II) and Zn(II) - Gupta, A.; Pannu, B.S. (Asian Journal of Chemistry, 2010)
The present paper describes the proton-ligand stability constants of disalicylamide and stability constants of its complexes with Co(II), Ni(II), Cu(II) and Zn(II).